Assessing Language Lecturer Preparedness for E-Learning Implementation - Asma, Asma (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2024)
The main aim of this study is to assess the preparedness of UIN Ar-Raniry language lecturers in executing e-learning. It seeks to ascertain whether psychological, technological, human resource, equipment, and content preparedness represent legitimate and trustworthy characteristics of e-learning preparedness. This study utilized the e-learning preparedness model established by Chapnick (2000) as its framework. The sample comprised 200 lecturers from the Language Development Center of UIN Ar-Raniry. The current study included three modified questionnaires derived from three primary sources: Teddy (2008), Trayek (2013), and Murphy, Coover, and Owen (1989). Thirty-seven items were included to assess the five constructs proposed in this study. This study employed descriptive statistics, including frequency counts and percentages. The study revealed that among 200 respondents, the majority supported the deployment of e-learning, indicating that most English and Arabic language instructors possess a greater level of preparedness for e-learning integration. The study concluded that lecturers at the UIN Ar-Raniry Language Development Centre are prepared to integrate e-learning into their pedagogical approaches. Consequently, it is recommended that UIN Ar-Raniry consolidate their efforts to improve the knowledge and skills of lecturers about content preparedness, technological preparedness, human resource preparedness, and equipment preparedness.